Stratifying chronic stroke patients based on the influence of contralesional motor cortices: An inter-hemispheric inhibition study. Issue 10 (October 2020) - Lin, Yin-Liang; Potter-Baker, Kelsey A.; Cunningham, David A.; Li, Manshi; Sankarasubramanian, Vishwanath; Lee, John; Jones, Stephen; Sakaie, Ken; Wang, Xiaofeng; Machado, Andre G.; Plow, Ela B.
Highlights: The relationship between interhemispheric inhibition and motor impairment is nonlinear (bimodal). We have defined a criterion of Upper Extremity Fugl-Meyer score of 43, which can be used for designing tailored treatments. Our results are in line with the bimodal-balance recovery model. Abstract: Objective: A recent "bimodal-balance recovery" model suggests that contralesional influence varies based on the amount of ipsilesional reserve: inhibitory when there is a large reserve, but supportive when there is a low reserve. Here, we investigated the relationships between contralesional influence (inter-hemispheric inhibition, IHI) and ipsilesional reserve (corticospinal damage/impairment), and also defined a criterion separating subgroups based on the relationships. Methods: Twenty-four patients underwent assessment of IHI using Transcranial Magnetic Stimulation (ipsilateral silent period method), motor impairment using Upper Extremity Fugl-Meyer (UEFM), and corticospinal damage using Diffusion Tensor Imaging and active motor threshold. Assessments of UEFM and IHI were repeated after 5-week rehabilitation (n = 21). Results: Relationship between IHI and baseline UEFM was quadratic with criterion at UEFM 43 (95%conference interval: 40–46). Patients less impaired than UEFM = 43 showed stronger IHI with more impairment, whereas patients more impaired than UEFM = 43 showed lower IHI with more impairment. Of those made clinically-meaningful functional gains in rehabilitation (n = 14), more-impaired patients showed further IHI reduction. Conclusions: A criterion impairment-level can be derived to stratify patient-subgroups based on the bimodal influence of contralesional cortex. Contralesional influence also evolves differently across subgroups following rehabilitation. Significance: The criterion may be used to stratify patients to design targeted, precision treatments.